Museum of never-never art, from part of life: arte, de parte de la vida - Latorre Carvajal, Gabriel (Rastros Rostros, 2002)
Every artist educator is a happy rider of astonishment. He rides in the endlessness of time, converses with history, unweaves labyrinths, builds geometries, portrays the face of life and reveals it to us iridescent, dissonant, harmonious and multiform.